Optimalisasi Desain Visual dalam Meningkatkan Brand Awareness UMKM Anfelin Patisserie - Mutiara Putri Maharani; Sridevi Qurani; Anggi Cahyani; Zulfahmi (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Anfelin Patisserie, a sweet food MSME founded by Fahira Atsilah in November 2023 in GOR H. Agus Salim, Padang. Initial observations show that Anfelin Patisserie, although known for its innovative products such as the viral "cookie bomb", still faces challenges in the visual representation of the brand, especially in the design of the banner and logo that is less than optimal.